Absorptive capacity in child welfare: a qualitative study with child welfare staff eliciting key factors for evidence-based practice adoption. Issue 5 (20th October 2022) - Winters, Andrew; Hooley, Cole; Gopalan, Geetha
ABSTRACT: Child Welfare (CW) provides an array of services to meet the needs of families, requiring agencies to be malleable in their ability to absorb new practices. Absorptive capacity (ACAP) refers to the routines and processes in which an organization acquires, assimilates, and applies new knowledge. ACAP has yet to be the focus of implementation research in CW settings. This exploratory study elicited feedback from CW staff in determining factors to consider when absorbing a new practice. Themes of logistic support, agency culture, and feedback from families emerged. Findings offer insights for CW agencies to consider when adopting a new practice.